3D bioprinting and nanotechnology in tissue engineering and regenerative medicine - Zhang, Lijie Grace; Fisher, John P.; Leong, Kam W. (Professor of biomedical engineering) (Academic Press, 2015)
3D Bioprinting and Nanotechnology in Tissue Engineering provides an in depth introduction to these two technologies and their industrial applications. Stem cells in tissue regeneration are covered, along with nanobiomaterials. Commercialization, legal and regulatory considerations are also discussed in order to help you translate nanotechnology and 3D printing-based products to the marketplace and the clinic. Dr. Zhang's and Dr. Fishers' team of expert contributors have pooled their expertise in order to provide a summary of the suitability, sustainability and limitations of each technique for each specific application. The increasing availability and decreasing costs of nanotechnologies and 3D printing technologies are driving their use to meet medical needs, and this book provides an overview of these technologies and their integration. It shows how nanotechnology can increase the clinical efficiency of prosthesis or artificial tissues made by bioprinting or biofabrication. Students and professionals will receive a balanced assessment of relevant technology with theoretical foundation, while still learning about the newest printing techniques. Includes clinical applications, regulatory hurdles, and risk-benefit analysis of each technology. This book will assist you in selecting the best materials and identifying the right parameters for printing, plus incorporate cells and biologically active agents into a printed structure Learn the advantages of integrating 3D printing and nanotechnology in order to improve the safety of your nano-scale materials for biomedical applications.